Prediksi cadangan air tanah berdasarkan hasil pendugaan geolistrik di Kabupaten Grobogan, Jawa Tengah - Ngudi Aji Jaka Yuwana; Nora Herdiana Pandjaitan; Roh Santoso Budi Waspodo (JURNAL SUMBER DAYA AIR, 2017)
One of the solutions for water shortage in Grobogan District is groundwater utilization. Excessive groundwater pumping will decrease groundwater level and trigger a landsubsidence. It is necessary to conduct hydrogeological study to determine the groundwater storage in this area. The purpose of this research were to determine the hydrogeological conditions, aquifer characteristics and potential of groundwater storage in Grobogan district. This research used geoelectrical method to identify rock characteristics. The results showed that the geological formation in Grobogan district consisted of Qa, Tmpk, Tmpl, Tps, Tmw and Qp. Grobogan district had 5 aquifers system, there are: poorly productive aquifers, moderately productive aquifers, locally productive aquifers, extensive productive aquifers and region without exploitable groundwater. The aquifer layer consisted of sand, marl sandy, silty sand and calcareous sand. The unconfined aquifer was located at 1,2 - 58 m from soil surface with average thickness of 13,54 m and the hydraulic conductivity of 3,54 m/day. The confined aquifer depth can be estimated between 29 - 174 m from soil surface with average thickness of 37,4 m and the hydraulic conductivity of 3,87 m/day.The predicted groundwater storage in Grobogan district of unconfined aquifer was 401,33 l/sec and confined aquifer was 1.804,95 l/sec.